HISTONE DEACETYLASE 6 suppresses salicylic acid biosynthesis to repress autoimmunity. Issue 4 (30th August 2021) - Wu, Zhenjiang; He, Lei; Jin, Ye; Chen, Jing; Shi, Huazhong; Wang, Yizhong; Yang, Wannian
Abstract: Salicylic acid (SA) plays an important role for plant immunity, especially resistance against biotrophic pathogens. SA quickly accumulates after pathogen attack to activate downstream immunity events and is normally associated with a tradeoff in plant growth. Therefore, the SA level in plants has to be strictly controlled when pathogens are absent, but how this occurs is not well understood. Previously we found that in Arabidopsis ( Arabidopsis thaliana ), HISTONE DEACETYLASE 6 (HDA6), a negative regulator of gene expression, plays an essential role in plant immunity since its mutation allele shining 5 ( shi5 ) exhibits autoimmune phenotypes. Here we report that this role is mainly through suppression of SA biosynthesis: first, the autoimmune phenotypes and higher resistance to Pst DC3000 of shi5 mutants depended on SA; second, SA significantly accumulated in shi5 mutants; third, HDA6 repressed SA biosynthesis by directly controlling the expression of CALMODULIN BINDING PROTEIN 60g ( CBP60g ) and SYSTEMIC ACQUIRED RESISTANCE DEFICIENT 1 ( SARD1 ). HDA6 bound to the chromatin of CBP60g and SARD1 promoter regions, and histone H3 acetylation was highly enriched within these regions. Furthermore, the transcriptome of shi5 mutants mimicked that of plants treated with exogenous SA or attacked by pathogens. All these data suggest that HDA6 is vital for plants in finely controlling the SA level to regulate plant immunity. Abstract : HISTONE DEACETYLASE 6 fine regulates salicylic acid level in plants by repressing its production to keep it at low levels under normal conditions and avoid its overaccumulation upon pathogen infection.